TAXONOMIC STUDIES ON GEOBLISSUS HIRTULUS (BURMEISTER) (HEMIPTERA : LYGAEIDAE) FROM INDIA - CHOPRA, N.P.; ., SUCHETA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Geoblissus hiritulus (Burmeister) has been recorded from Bihar, India for the first time. Detailed description and appropriate illustrations are provided for its identification.